Selected chronic diseases and their risk factors in teachers - Alicja Bortkiewicz; Agata Magdalena Szyjkowska; Jadwiga Siedlecka; Teresa Makowiec-Dąbrowska; Elżbieta Gadzicka (Nofer Institute of Occupational Medicine, 2020)
Chronic diseases (ChDs) pose an essential problem from an individual, social and economic point of view. It is estimated that they account for 60% of all deaths worldwide, and this share is expected to rise to 72% by 2020. The most prevalent are cardiovascular diseases (30%), cancers (13%), respiratory diseases (7%), and diabetes (2%). Their major risk factors include unhealthy diet, the lack of physical activity, and tobacco smoking. Of significance are also occupational and environmental hazards. Among teachers, the factor with the highest impact is noise, reported by 25% of male and 38% of female teachers. In Poland, there are no databases on ChDs or risk factors in teachers; only voice disorders are well-recognized as an occupational disease. Only a few studies of health and lifestyle were conducted among teachers in Poland, but they cannot be generalized because they were carried out with different methods, in small groups of people and in various regions in the country. A representative study carried out by Statistics Poland (GUS) among education employees (with no separate data for teachers) revealed that the most prevalent were musculoskeletal disorders, including back-pain (21.9%), as well as painfulness of the neck, shoulder, hand, hip and leg (10% in each case). Headaches and eye fatigue were found in 14.6%; stress, anxiety and depression in 7.3%; and cardiovascular disorders in 4.6% of the study population. Defining health problems in this professional group is an important public health issue which should enable reducing the prevalence and adverse health effects of ChDs. Med Pr. 2020;71(2):221-31